Demographic profile and real world data of persons with hemophilia in a resource constrained setup - M Joseph John; Tanuja Tanuja; Amrith Mathew; Chepsy C Philip; Jasprit Singh; Mullai Dinakaran; G D Vandhiyadevan; Santhosh Mathangi; Suvir Singh; Ranjeet Singh Mashon; Naveen Kakkar (Wolters Kluwer Medknow Publications, 2018)
Background: Hemophilia is underdiagnosed in India, and there is lack of state specific data on the extent and morbidity. This article provides the real world demographic and clinical data of patients with hemophilia (PwH) in a resource-constrained setting in Punjab, India. Patients and Methods: This is a retrospective analysis of PwH in the institutional hemophilia registry over 9 years. Eligible patients who had a confirmed diagnosis at our institute were included in the analysis. Demographic, clinical, and treatment data used in the current analysis were extracted from medical records using a standardized data collection form. Results: A total of 211 patients were from Punjab, comprising 175 PwH A (91.3%) and 36 with PwH B for uniformity. The mild, moderate, and severe hemophilia in the cohort were 32 (15.1%), 45 (21.3%), and 132 (62.5%), respectively. No patient was on continuous prophylaxis. Inhibitors were positive in 7.9% of patients. Joint deformity was found in 83.5% of severe PwH. Transfusion-transmitted infections were found in 24 (18.3%). There were no statistically significant differences between hemophilia A and B groups with regard to demographic or clinical characteristics. The current median age of the group was 22 years against a national average of 27.6 years. Only 7.4% of the estimated cases of PwH are diagnosed in Punjab. Conclusion: There are significant underdiagnoses, increased incidence of transfusion-transmissible infection, and joint deformity among PwH in Punjab. Therefore, it warrants an immediate need to develop a registry, increase awareness about hemophilia, and provide comprehensive care.